Influences of Long-Term Tectonic and Geo-Climatic Effects on Geotechnical Problems of Soft Ground - Ulaanbaatar, Mongolia - S. Manandhar; T. Hino; K. Kitagawa (Lowland Technology International, 2016)
Ulaanbaatar city situates in Ulaanbaatar Folded System with presence of Mongolo-Baikal seismic zone. The presence of the Tuul River Valley dissected the basin with the formation of soft sediments transported by fluvial and Aeolian environments. The presence of scattered permafrost soil due to geo-climatic condition has led to freeze-thaw phenomena by physical weathering of the ground. This study reveals the influences of long-term tectonic and geo-climatic effects have brought up geotechnical problems in the area. Further it is advised that special attention need to be given in settlement of the area associated with mechanical disintegration of the ground, characterizing similar with lowlands along the valley bottom.